Attitudes to health and work amongst the working-age population - Collingwood, Suchi (London, 2011)
"This report presents findings from a module within the Office of National Statistics (ONS) Opinion Omnibus Survey that focussed on collecting data on the attitudes of the working-age population towards the relationship between work and health. The final set of questions covered several areas including: